Delight or Poison - Tőtős Dorottya (Hungarian Studies Yearbook)
For most of the 20th century, Hungarian literary history disregarded decadence as a thematic or stylistic marker and refused to acknowledge that it was a significant cultural driving force of the fin-de-siècle Hungarian literature. I propose to interpret decadence not as a mere stylistic, moral or temporal category, but as a cultural trope, a modernist way of perceiving the world and creating art. I hypothesize that the Hungarian reception of French and English decadence at the end of the 19th century produced a uniquely reflexive version of this phenomenon. I aim to understand how decadence integrates into and presents itself in Hungarian literature and to uncover significant works hidden by the cultural forgetfulness of Hungarian literary history.